Front Cover: Mechanistic Studies on the Epoxidation of Alkenes by Macrocyclic Manganese Porphyrin Catalysts (Eur. J. Org. Chem. 35/2022). Issue 35 (15th September 2022) - Chen, Xiaofei; Duez, Quentin; Tripodi, Guilherme L.; Gilissen, Pieter J.; Piperoudis, Dimitrios; Tinnemans, Paul; Elemans, Johannes A. A. W.; Roithová, Jana; Nolte, Roeland J. M.
Abstract : The Front Cover illustrates the separation of isomeric manganese oxo‐intermediates by ion mobility mass spectrometry. The manganese oxo‐intermediates are generated during the epoxidation of alkenes by iodosylbenzene, catalyzed by manganese porphyrin cage complexes. These intermediates are formed either on the inside or outside of the cage complex. Cover designed by Quentin Duez. More information can be found in the Research Article by J. A. A. W. Elemans, J. Roithová, R. J. M. Nolte et al .